View of Campus, 1940 (1940)
View of campus, 1940. View of the P. Also can see Weeks First Administration Buildings, Heron Hall, Chase Hall, Deuel Hall, Jespersen/'Jesperson' Hall (Dormitory Row), Power House, Crandall Gym. View from Radio Tower Hill.